The Searching for Self-Identity in Kazuo Ishiguro’s Never Let Me Go - Rahmi Munfangati; Aisyah Nur Handayani (IAIN MADURA, 2021)
Self-identity is an aspect that every human in the world has. Without it, a person is in danger of being negatively affected by those around him/her and by the outside world. Some people are grappling with this identity-forming phase in their search for self-definition. This is reflected in Never Let Me Go by Kazuo Ishiguro. Therefore, this research aims to describe the main characters' search for self-identity as seen in the novel. The type of this research was library research. This research applied a psychological approach, and the data were analyzed using the descriptive qualitative method. The results showed that Kathy and Tommy's quest to find their true selves occurred in childhood, adolescence, and adulthood stages. Narrated by Kathy, she flashed back the memories of how they, Kathy and Tommy, are puzzled because of too many mysteries in Hailsham, the boarding school where they live. They connected each puzzle which could be the answer. But, in the novel, the question they belong to for being different brought them to another question. The process of findings itself flowed as long as they grew. In the end, they found information about their identity as a clone and as an individual.